Adjuvant Chemotherapy and Tumor Sidedness in Stage II Colon Cancer: Analysis of the National Cancer Data Base - Mukkamalla, Shiva Kumar R.; Huynh, Donny V.; Somasundar, Ponnandai S.; Rathore, Ritesh (Frontiers in Oncology, 2020)
Background Current guidelines recommend discussion of adjuvant chemotherapy (AC) for stage II colon cancer (CC) with high-risk features despite lacking conclusive randomized trial data. We examined AC administration in this population and its effect on overall survival (OS) for available patient, tumor and treatment characteristics Methods Using National Cancer Data Base, a cohort of 42,971 stage II CC patients diagnosed from 2004-2009, who underwent surgery with curative intent, was identified. Chi-square test and multivariate logistic regression were used to analyze baseline characteristics and to calculate odds of chemotherapy administration, respectively. Survival analysis was conducted using Kaplan Meier survival analysis with log-rank test and Cox proportional hazards regression modelling.. Results AC was administered to 26% patients. The use decreased with advancing age and elderly patients received more single-agent than multi-agent chemotherapy (3% vs 2.4%, p <0.0001). Major predictors of AC use included pT4 status, evaluation of <12 lymph nodes, high grade tumors, positive resection margins, age <65 years, left sided tumors, and low comorbidity score. AC was associated with improved OS regardless of high-risk features (pT4, undifferentiated histology, <12 lymph node evaluation or positive resection margins), tumor location, age, gender, comorbidity index, chemotherapy regimen or type of colectomy (adjusted HR: single-agent 0.55, multi-agent 0.6; p <0.0001). In subgroup analysis, AC use compensated for the survival differences otherwise seen between left and right sided tumors in the non-chemotherapy population. Conclusion AC in stage II CC was associated with improved OS regardless of age, chemotherapy type or high-risk features. It improved 5-year OS irrespective of tumor location and seemed to compensate for the survival difference seen between right and left sided tumors noted in the non-chemotherapy group.